2017
DOI: 10.1093/ejcts/ezx056
|View full text |Cite
|
Sign up to set email alerts
|

Management of cerebral malperfusion in surgical repair of acute type A aortic dissection

Abstract: Perioperative cerebral perfusion should be carefully managed, especially in the patients with preoperative neurological symptoms or partial or complete thrombosis of the SABV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 20 publications
1
34
2
Order By: Relevance
“…In Table 1, it summarized observational single center experience focusing on neurological outcomes after TAAAD (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
“…In Table 1, it summarized observational single center experience focusing on neurological outcomes after TAAAD (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
“…Furukawa et al reported that partial or complete thrombosis of the supra-aortic branch vessels is an independent risk factor of perioperative cerebral malperfusion. 16) Most patients in the young group had completely patent false lumen. Thus, the incidence of cerebral malperfusion due to thrombosis at the false lumen of the supra-aortic branch vessels is low.…”
Section: Discussionmentioning
confidence: 96%
“…The rate of TAR was equal or higher than that in previous reports (15%-48%). 1,2,[13][14][15][16] However, whether extensive aortic replacement should be performed in the emergency setting still remains controversial. Di Eusanio et al reported that TAR is one of the independent risk factors for in-hospital mortality on the basis of the complete International Registry of Aortic Dissection (IRAD) database (1,995 surgery patients from January 1996 to January 2013).…”
Section: Discussionmentioning
confidence: 99%
“…and (3) available postoperative brain CT data. Exclusion criteria included (1) previous aortic surgical history (n = 16); (2) history of old cerebral infarction or hemorrhagic stroke (n = 7); (3) unevaluable CTA images (n = 7); (4) interval from admission to surgery of > 24 hours (n = 31); (5) without preoperative DWI examination (n = 76); and (6) postoperative nonneurogenic death (n = 12). A total of 149 patients were excluded.…”
Section: Patientsmentioning
confidence: 99%
“…[1] Despite numerous innovations in contemporary perioperative anesthetic and surgical management, stroke after surgical treatment of ATAAD remains high, ranging from 2.9-30.4% in published series. [2][3][4][5][6][7][8] Previous reports described that preoperative cerebral malperfusion in patients with ATAAD is a predictor for postoperative stroke and detrimental outcome. [9][10][11] Cerebral malperfusion was diagnosed if patients with ATAAD had neurological symptoms and signs with ultrasonography or radiographic evidence of dissection of the corresponding aortic branch vessel.…”
Section: Introductionmentioning
confidence: 99%